Cognitive Methods: How the Use of the Free Inquiry Learning Model Increases Students' Cognitive Empathy in Science Learning - Octaviani*, Firda Katrina; Faizah, Ulinnuha Nur; Kamarudin, Nurzatulshima (Jurnal IPA & Pembelajaran IPA, 2025)
Education research continues to develop, one of which is related to the application of appropriate learning models to improve the quality of learning. The free inquiry learning model in science learning can train students to understand scientific concepts, as well as improve students' cognitive empathy. This study aims to analyze the effect of the application of the free inquiry learning model with a cognitive method approach on improving students' cognitive empathy in science learning. This study uses a quantitative method with a quasi-experimental design, where the pretest and posttest were conducted in the experimental class and the control class. The sample used in the experimental class was 18 students, while the control class was 18 students. Data processing using normality tests, homogeneity, paired t-tests, and Anova tests. The results of this study indicate that the free inquiry learning model with a cognitive method approach has an effect on students' cognitive empathy in science learning with a t-test result of 0.000. This study will support the development of learning strategies to improve students' cognitive empathy